جريمة الابتزاز عبر وسائل التواصل الاجتماعي في المملكة العربية السعودية : دراسة تحليلية للقانون الواجب تطبيقه وتحدياته - حريز، محمد سالم سلطان (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2020)
This research paper explains the extortion crime using the social media in Saudi Arabia and how important our role, reaction, feeling to protect our current and upcoming generations. The massive revolution of technology and social media have positively affected the worldwide especially in expedite our formal, commercial, or informational transaction as it saves time, efforts, and consider a cost-effective establishment in all settings. Although many generations with different ages are involved with the social media revolution and using it safely in their daily life at work, study, and entertainment, some are not; especially when they are using it to blackmail others either to have a financial advantage, to hurt them morally, or even to have a specific information as it was explained in details in this research and how other researches findings' tackled it. The best previous researches findings', ideas, recommendations that support this interesting topic were carefully selected and were studied in depth. The method of this research was used descriptive analytical approach in which a comprehensive system related to extortion crimes and cases will be presented and analyzed in courts. The conclusion and the recommendation of this research paper are to support other researcher's gap in their studies and/ or to enlighten other individuals; researchers; and communities, and to increase the awareness of using social media safely and avoid the use of suspected sites and/ or individuals who put others' life at risk. In addition, this study has reach most important result which strict punishment laws and regulations to those who committed extortion crimes has to be applied and it has to be updated based on recent development in laws and information fighting system, thus more protection for individual, community, and national level will be maintained.